2010
DOI: 10.1017/s146114571000057x
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and protein synthesis inhibitors reduce the induction of behavioural sensitization to a single morphine exposure and regulate Hsp70 expression in the mouse nucleus accumbens

Abstract: New protein synthesis has been implicated as necessary for long-lasting changes in neuronal function. Behavioural sensitization to a single exposure to addictive drugs is a form of neuroplasticity, but little is known about the importance of new protein synthesis in the underlying mechanism. This study was designed to investigate the effects of the transcription inhibitor actinomycin D (AD) and the protein synthesis inhibitor cycloheximide (CHX) on induction of behavioural sensitization to a single morphine ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 64 publications
5
16
0
Order By: Relevance
“…The locomotor-stimulating effects of 32 and 100 mg/kg morphine increased during repeated administration in the first experiment, consistent with other findings of locomotor sensitization after administration of morphine in rats (Vanderschuren et al 2001) and mice (Valjent et al 2010; Luo et al 2011; Koek 2013). These short-term effects of repeated administration of morphine on locomotion were similar in adolescents and adults, confirming and extending previous observations (Koek 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The locomotor-stimulating effects of 32 and 100 mg/kg morphine increased during repeated administration in the first experiment, consistent with other findings of locomotor sensitization after administration of morphine in rats (Vanderschuren et al 2001) and mice (Valjent et al 2010; Luo et al 2011; Koek 2013). These short-term effects of repeated administration of morphine on locomotion were similar in adolescents and adults, confirming and extending previous observations (Koek 2013).…”
Section: Discussionsupporting
confidence: 90%
“…Traditionally, behavioural sensitization was induced by repeated, intermittent drug exposures. Amazingly, even a single drug exposure, such as an exposure to amphetamine (Robinson et al, 1982;Vanderschuren et al, 1999), cocaine (Kalivas and Alesdatter, 1993), morphine (Vanderschuren et al, 2001;Jing et al, 2011;Luo et al, 2011;Qin et al, 2013) and nicotine (Bhatti et al, 2007) can also evoke behavioural sensitization. Although the extent of behavioural sensitization induced by a single drug exposure is not as profound as that induced by multiple drug exposures, the enduring behavioural and neurochemical consequences of single and repeated drug exposures appear to be highly comparable (Vanderschuren et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, repeated drug exposure with long intervals is more effective to induce sensitization as compared to chronic exposure to either high and/or escalating dosage with short intervals [17, 23]. Interestingly, even a single exposure to cocaine [5, 7], amphetamine [18, 22] and morphine [6, 10, 21] can produce long-lasting behavioral and neurochemical sensitization.…”
mentioning
confidence: 99%
“…Not surprisingly, when the METH dose was further increased to 2 mg/kg, a higher sensitization was observed under both conditions. Previously, it has also been suggested that the mangnitude of sensitization was linearly related to the pretreatment dose in both single [10] or repeated treatment schedules [1] for morphine-induced behavioral sensitization. Kitanaka et al explored the functional alterations of monoaminergic neuronal systems in mice after single and repeated injection of METH, which showed that the degree and direction of modification of the monoaminergic metabolism depend on the treatment (single or repeated) and on the brain regions [8].…”
mentioning
confidence: 99%